The collected writings of Franz Liszt. - Liszt, Franz, 1811-1886 (Scarecrow Press, 2011)
This translation is the starting volume of Janita Hall-Swadley's The Collected Writings of Franz Liszt, the very first production of Liszt's entire literary collection in English. In Volume 1, Liszt provides insight into Chopin's early childhood and musical development, the cultural traditions and customs that inspired the polonaises and mazurkas, and the final days and hours of the composer before he died. It includes a thorough discussion of Liszt as an author and the tainted past that surrounded his writings beginning.